Industria 4.0 y Manufactura Digital: Un Método de Diseño Aplicando Ingeniería Inversa - Carro Suárez, Jorge; Flores Salazar, Fabiola; Flores Nava, Irma; Hernández Hernández, Ramón (Ingeniería, 2019)
Context: This research presents a review of literature and current state of the Industry 4.0 and Reverse Engineering process with the aim of proposing a design method for the digitization and manufacturing of 3D parts through the use of Digital Manufacturing. Method: A theoretical and systematic review about Industry 4.0 and Reverse Engineering is carried out to determine the relationship between them. Subsequently, several published design methods are analyzed to select one as a reference. Finally, according to the results obtained from the theoretical analysis a proposal of the design method to perform the digitization and manufacture of a 3D piece. The application of the proposed method is validated with the digitalization of one piece and its 3D modeling and printing. Results: We identified that the relationship between Industry 4.0 and Reverse Engineering is the Additive Manufacturing and that the ideal design method for the development of the research is the Archer’s model through the perspective of Liu & Boyle, since the proposed model will focus on designer through a process of digitalization. Finally, its application demonstrates its relevance, considering that nowadays the Digital Manufacturing must be a determinant component for Industry 4.0 Conclusions: The conditions, particularities and operating costs of the new processes applied by Industry 4.0 imply the need to consider new models to generate benefits for companies in order to become more competitive, profitable and sustainable companies on a global scale. In this context, Digital Manufacturing is presented as an alternative design, which although it has been applied for years, it has not been recognized as a new technological trend, so its inclusion on Industry 4.0 is relevant and necessary.